Condiciones pre-eruptivas del edificio volcánico Santa Helena, Complejo Volcánico Doña Juana, Colombia (2020)
Mineral geochemistry data acquired by electronic microprobe analysis was obtained, processed classified and analyzed for amphiboles, plagioclase feldspars, pyroxenes and Fe-Ti oxides from lava flow samples associated with the first eruptive epoch of Doña Juana Volcanic Complex (SW Colombia). By analyzing their classification, compositional variations and evolutionary paths, together with the verification of equilibrium states and the integration of petrographic and geothermobarometric information, new evidence was obtained which supports hypotheses regarding the effect of magma mixing in the plumbing system of the first volcanic edifice of the complex. From the gathered information, events of variation in temperature, pressure and composition associated with magma mixing are proposed as possible triggers for the eruptive events of the considered epoch.